Kontribusi Para Ilmuwan Muslim Dalam Bidang Ilmu Akuntansi - Warto Warto (Prodi Perbankan Syariah FAI UMT, 2020)
The blurring of history in the field of science often occurs. In the 18th century AD Adam Smith wrote an economic theory in the book